2020
DOI: 10.1007/jhep12(2020)040
|View full text |Cite
|
Sign up to set email alerts
|

Dual description of η-deformed OSP sigma models

Abstract: We study the dual description of the η-deformed OSP(N|2m) sigma model in the asymptotically free regime (N > 2m + 2). Compared to the case of classical Lie groups, for supergroups there are inequivalent η-deformations corresponding to different choices of simple roots. For a class of such deformations we propose the system of screening charges depending on a continuous parameter b, which defines the η-deformed OSP(N|2m) sigma model in the limit b → ∞ and a certain Toda QFT as b → 0. In the sigma model regim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…It would be interesting to study the chiral limits of these coset theories using techniques similar to the ones developed in this paper. For instance, relevant examples in this context might be the conformal limits of Yang-Baxter deformations of the OpN q sigma models and their supersymmetric version, which have been the subject of recent works in the literature [94][95][96], and of the integrable coset sigma models on G ˆG{H [97-100] whose conformal limit is the Guadagnini-Martellini-Mintchev CFT [101].…”
Section: More General Chiral Limits Of Affine Gaudin Modelsmentioning
confidence: 99%
“…It would be interesting to study the chiral limits of these coset theories using techniques similar to the ones developed in this paper. For instance, relevant examples in this context might be the conformal limits of Yang-Baxter deformations of the OpN q sigma models and their supersymmetric version, which have been the subject of recent works in the literature [94][95][96], and of the integrable coset sigma models on G ˆG{H [97-100] whose conformal limit is the Guadagnini-Martellini-Mintchev CFT [101].…”
Section: More General Chiral Limits Of Affine Gaudin Modelsmentioning
confidence: 99%
“…The RG flow of these models depends on the difference of N − 2m. It was shown in [30] that in the regime of purely imaginary η = iκ they are asymptotically free if N − 2m > 2, conformal if N − 2m = 2 and infrared free if N − 2m < 2. There was also analyzed the UV limit of these theories for N − 2m > 2, which can be understood as a free theory perturbed by a set of operators assembled from certain screening charges.…”
Section: Discussionmentioning
confidence: 99%
“…Putting (A.14), (2.2), (2.3) and (2.4) into (A.8), we derive a set of equations for the unknown coefficients b(L) k . These equations are too cumbersome to be written here, but can be easily solved and here we write just the solution for the two-and three-loop orders b(2) It is rather natural to expect that integrable deformed sigma models in the UV limit can be understood as a Gaussian theory perturbed by certain relevant operators (see for example discussions in [30]). These operators are constrained by the integrable structure of the QFT and are built from the screening charges.…”
Section: Discussionmentioning
confidence: 99%
“…The RG flow of these models depends on the difference of N − 2m. It was shown in [39] that in the regime of purely imaginary η = iκ they are asymptotically free if N − 2m > 2, conformal if N − 2m = 2 and infrared free if N − 2m < 2. There was also analyzed the UV limit of these theories for N − 2m > 2, which can be understood as a free theory perturbed by a set of operators assembled from certain screening charges.…”
Section: Jhep01(2022)043 4 Concluding Remarksmentioning
confidence: 99%
“…In the work [34] it was shown that integrable deformed O(N sigma models in the UV limit can be understood as a Gaussian theory perturbed by certain relevant operators (for the OSp(N |2m) sigma models see the discussion in [39]). These operators are constrained by the integrable structure of the sigma model and are built from the screening charges.…”
Section: B Deformed O(3) Sigma Model Screening Chargesmentioning
confidence: 99%